Poverty – Socio-Economic Determinants and Consequences - Janicki, Tadeusz (Studia Historiae Oeconomicae, 2025)
The current volume of Studia Historiae Oeconomicae focuses on analysing poverty as a widespread and multidimensional phenomenon, rooted in long-term socio-economic processes. It varies greatly depending on location, era, and political system. The volume offers a range of research approaches, from theoretical and methodological discussions on the categories of destitution and poverty, to case studies on Central and Eastern European countries and Nigeria, as well as the issue of poverty among Polish émigrés in France during the 19th century. The contributions are united by a shift away from a purely descriptive view of poverty towards explaining its causes, mechanisms and consequences, drawing on insights from sociology, economics, anthropology and political science. Consequently, the volume monstrates the potential of interdisciplinary research to deepen understanding of economic diversity, including poverty as a key element of both historical and current social challenges.